The Quality of Statistical Data in the Context of User Needs and Expectations - ZAIETS, S. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
Meeting the needs and demands of consumers of statistical information requires appropriate tools to systematically determine the potential, strengths and weaknesses of state statistical institutions, as well as the risks associated with this. In this regard, the assessment of the quality of statistical information by data users is one of the key areas of work of the statistical service in modern conditions. The aim of the study is to consider approaches to assessing users’ needs for high-quality statistical information in the context of global, national and information challenges of our time. The article explores ways to identify the needs of users of statistical information, summarizes the results of questionnaires, which are an integral part of quality reports. The components of the evaluation of the use of open data of the Open Data Barometer rating are analyzed, based on surveys during state self-assessment, expert assessment, and secondary data. The leading positions and bottlenecks of Ukraine in the implementation of open data sets have been identified. The advantages are considered and proposals for improving the Methodology for calculating the user satisfaction index of statistical information, which is introduced by the State Statistics Service of Ukraine in order to meet the needs and demands of consumers of statistical information, are presented. The experience of other countries on assessing the level of user satisfaction with services, which should be used in a comprehensive assessment of various aspects of the domestic statistical service and various characteristics of statistical information for users, such as understanding materials, visual presentation of information, ease of use, and more, is considered. The results of the study allowed us to provide suggestions on the need to transform the domestic statistical service into a coordinating center for the distribution of verified, processed and standardized data sets available for identification using open catalogs and data lists based on strategic partnerships with data providers, technology providers, scientists, researchers and the media.